Judicial Disparities in Determining Children Born Out of Wedlock: Examining Legal Reasoning Between Administrative Needs and Sharia-Based Justice - Mughniatul Ilma; Khusniati Rofiah; Asma' 'Alilatul Barizah Irfani (Legitima : Jurnal Hukum Keluarga Islam, 2026)
Purpose – This article examines the disparity in judges' reasoning in the determination of children born out of wedlock in the Religious Court environment, with an emphasis on how judges build legal reasoning when facing the tension between administrative needs and sharia-based justice. This research aims to shift the focus of analysis from the decision's results alone to the reasoning structure that shapes the decision and its implications for legal clarity and child protection. Design/methods/approach – This study uses a normative juridical approach with a comparative case study of the three determinations of the Ponorogo Religious Court. Data were obtained from decision documents, classical and contemporary fiqh literature, and a limited number of interviews with judges. The analysis was carried out using the framework of legal pluralism, judicial discretion, and legal reasoning to capture the interaction of various norm systems in judicial practice. Findings – The results of the study show that the disparity is more attributable to differences in judges' reasoning than to differences in decision outcomes. These variations form a spectrum of approaches that reflect different degrees of integration between state law, fiqh principles, and practical considerations. The level of elaboration of legal implications, especially regarding nasab, inheritance, and guardianship, affects the clarity of the law and the decision's educational function. Research implications/limitations – This study confirms the importance of analyzing judges' reasoning in Islamic family law, but it is limited by the number of cases and specific locations. Further research can expand the scope through a comparative or socio-legal approach. Originality/value – This article offers a typology of judges' reasoning as an analytical contribution to understanding the disparity of judgments, showing that this disparity is a manifestation of legal pluralism and judicial discretion, and emphasizing the importance of the educational function of judgments in bridging state law and Islamic law.